Structure of the Brzozówka River valley in the light of geophysical and geological study, NE Poland - Żurek, Krzysztof; Kalicki, Tomasz (Acta Geographica Lodziensia, 2021)
The meandering Brzozówka River, a left tributary of the Biebrza River, is located in the Podlasie Voivodship of north-eastern Poland. It flows in a wide, N–S-oriented glacial depression between Goniądz and the Suchowola-Janików Upland. The valley floor is filled with peat. GPR surveys were conducted to recognise the geological structure of the bottom of the depression, determining the peat thickness and the top of its mineral base. The GPR cross-section crossing the Brzozów-ka River valley in an E–W direction consists of 21 echograms with a total length of 3 525 m. Anomalies were recorded at different levels on the echograms. An undulated top of mineral basement covered by a layer of organic sediments was identified. Several segments of different age and structure can be distinguished within the valley bottom: the Vistulian sandy gravel terrace, the Holocene peat plain (peats lie on the undulated top of mineral sediments, which may be palaeochannel remnants of a Pleistocene braided system) and the Holocene alluvia of a meander belt. The last, fluvial segment comprises only 10% of the whole valley bottom width, which allows us to consider the Brzozówka River valley as an underfit valley.